2016
DOI: 10.1038/srep39619
|View full text |Cite
|
Sign up to set email alerts
|

The direct-to-indirect band gap crossover in two-dimensional van der Waals Indium Selenide crystals

Abstract: The electronic band structure of van der Waals (vdW) layered crystals has properties that depend on the composition, thickness and stacking of the component layers. Here we use density functional theory and high field magneto-optics to investigate the metal chalcogenide InSe, a recent addition to the family of vdW layered crystals, which transforms from a direct to an indirect band gap semiconductor as the number of layers is reduced. We investigate this direct-to-indirect bandgap crossover, demonstrate a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
169
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(182 citation statements)
references
References 34 publications
13
169
0
Order By: Relevance
“…This conclusion is also confirmed by photoluminescence (PL) measurements since a bandgap-related emission was observed for both samples. It is worth noting that PL for such crystals was reported by other authors, see for example refs 5255 , and therefore emission properties are not further discussed in this work. In addition, the MR spectrum observed for InSe is very consistent with previous photoreflectance studies of γ-InSe 56 .…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…This conclusion is also confirmed by photoluminescence (PL) measurements since a bandgap-related emission was observed for both samples. It is worth noting that PL for such crystals was reported by other authors, see for example refs 5255 , and therefore emission properties are not further discussed in this work. In addition, the MR spectrum observed for InSe is very consistent with previous photoreflectance studies of γ-InSe 56 .…”
Section: Resultsmentioning
confidence: 84%
“…In addition, the MR spectrum observed for InSe is very consistent with previous photoreflectance studies of γ-InSe 56 . The bulk InSe sample studied in this work is also γ-polytype (i.e., 2H polytype according to the nomenclature used in this work) and extended studies on exfoliated layers from such crystal can be found in refs 54,55 . The oscillating signal below the band gap is due to F-P oscillations with a short period.…”
Section: Resultsmentioning
confidence: 99%
“…This is based on observations of their optical properties, which can differ strongly from those of their parent bulk materials, and which have demonstrated room-temperature electroluminesence 28 , strong photoresponsivity 23 with a broad spectral response 26,27,29 , and band gap tunability 24 . Recent studies of luminescence 30 and magnetoluminescence 31 in InSe have shown a strong dependence of the band gap on the number of layers, from ∼ 2.8 eV for the monolayer to ∼ 1.3 eV for thick films. These experiments have identified two main photoluminescence lines, interpreted 30 as a lower energy transition between bands dominated by s and p z orbitals (A-line) and hot luminescence, involving holes in a deeper valence band based on p x and p y orbitals (B-line).…”
Section: Introductionmentioning
confidence: 99%
“…The thicknesses of the encapsulated InSe flakes range from 20 nm to 2.4 nm, corresponding to around 24 atomic layers to 3 layers [8]. The thickness was measured using atomic force microscopy, as shown in figure 1b.…”
Section: Sample and Methodsmentioning
confidence: 99%